Early Versus Late Tracheostomy in Patients With Acute Traumatic Spinal Cord Injury: A Systematic Review and Meta-analysis. (February 2021) - Mubashir, Talha; Arif, Abdul A.; Ernest, Prince; Maroufy, Vahed; Chaudhry, Rabail; Balogh, Julius; Suen, Colin; Reskallah, Alexander; Williams, George W.
Abstract : BACKGROUND: Acute traumatic spinal cord injuries (SCIs) often result in impairments in respiration that may lead to a sequelae of pulmonary dysfunction, increased risk of infection, and death. The optimal timing for tracheostomy in patients with acute SCI is currently unknown. This systematic review and meta-analysis aims to assess the optimal timing of tracheostomy in SCI patients and evaluate the potential benefits of early versus late tracheostomy. METHODS: We searched Medline, PubMed, Embase, Cochrane Central, Cochrane Database of Systematic Reviews, and PsycINFO for published studies. We included studies on adults with SCI who underwent early or late tracheostomy and compared outcomes. In addition, studies that reported a concomitant traumatic brain injury were excluded. Data were extracted independently by 2 reviewers and copied into R software for analysis. A random-effects meta-analysis was performed to estimate the pooled odds ratio (OR) or mean difference (MD). RESULTS: Eight studies with a total of 1220 patients met our inclusion criteria. The mean age and gender between early and late tracheostomy groups were similar. The majority of the studies performed an early tracheostomy within 7 days from either time of injury or tracheal intubation. Patients with a cervical SCI were twice as likely to undergo an early tracheostomy (OR = 2.13; 95% confidence interval [CI], 1.24–3.64; P = .006) compared to patients with a thoracic SCI. Early tracheostomy reduced the mean intensive care unit (ICU) length of stay by 13 days (95% CI, −19.18 to −7.00; P = .001) and the mean duration of mechanical ventilation by 18.30 days (95% CI, −24.33 to −12.28; P = .001). Although the pooled risk of in-hospital mortality was lower with early tracheostomy compared to late tracheostomy, the results were not significant (OR = 0.56; 95% CI, 0.32–1.01; P = .054). In the subgroup analysis, mortality was significantly lower in the early tracheostomy group (OR = 0.27; P = .006). Finally, no differences in pneumonia between early and late tracheostomy groups were noted. CONCLUSIONS: Based on the available data, patients with early tracheostomy within the first 7 days of injury or tracheal intubation had higher cervical SCI, shorter ICU length of stay, and shorter duration of mechanical ventilation compared to late tracheostomy. The risk of in-hospital mortality may be lower following an early tracheostomy. However, due to the quality of studies and insufficient clinical data available, it is challenging to make conclusive interpretations. Future prospective trials with a larger patient population are needed to fully assess short- and long-term outcomes of tracheostomy timing following acute SCI.